Impact of Implementation of Balanced Business Score Card (BBSC) on Organizational Effectiveness : A Case Study of Bharat Sanchar Nigam Ltd (BSNL) - Makkar, Urvashi; Kumar, Harinder (Prabandhan: Indian Journal of Management, 2011)
Achieving excellence is, since ages, a driving force for every organization. Few can doubt the scale and complexity of issues that organizations face if they are to be successful in the 21st century. To achieve this success, business leaders will have to address emerging global issues such as electronic commerce, industry convergence, worldwide alliances, virtual organizations and corporate citizenship. But even more importantly, they will need to find new ways to excel at the fundamentals of business: leadership, management, strategy and implementation, irrespective of the area of operation. Organizational effectiveness is the concept of how effective an organization is in achieving the outcomes the organization intends to produce. Organizations are under growing pressure to demonstrate effective management, provide greater accountability, and accomplish more with fewer resources to improve their effectiveness.